Integrated distilled spent grain with husk utilization: Current situation, trend, and design. (June 2023) - Ma, Yan-Chao; Zheng, Yang; Wang, Li-Hua; Sun, Bao-Guo; Zhao, Mou-Ming; Huang, Ming-Quan; Wu, Ji-Hong; Li, He-He; Sun, Xiao-Tao
Abstract: Distilled spent grain with husk (DSGH) is a solid by-product of Chinese Baijiu industry, with an annual output of more than 30 million tons. Due to the lack of widely applicable utilization models, it has caused environmental pollution and resource waste. As a biomass resource, reasonable utilization of DSGH is attracting attention. However, the utilization of DSGH is rarely reviewed comprehensive. There are 12 flavor-styles in Baijiu, of light, strong, and soy sauce flavor-styles of Baijiu account for over 90% of the market share, they contribute to the vast majority of DSGH's output. This review introduces the brewing process of solid-state fermentation Baijiu and the origin of DSGH, analyzes the development trend of Baijiu industry in recent years, and its impact on the recycling and utilization of DSGH, and a formula for calculating the yield of DSGH is proposed for the first time. Then, the research progresses of 10 utilization methods of DSGH has been comprehensively summarized and is divided into two aspects: nutrition and health, and materials and energy. After analyzing the advantages and disadvantages of these methods, the future development directions are proposed. Finally, a fractionation cascade process design proposal is put forward, which can complement the shortcomings of different utilization methods, reduce resource waste, and has the potential to produce up to eight industrial products simultaneously, broadening the product chain. This will help Baijiu enterprises achieve rapid treatment and high-value utilization of DSGH, so as to realize clean production. Graphical abstract: Image 1 Highlights: Source of DSGH was elucidated based on Baijiu's processing and flavor-style. Development trend of Baijiu industry and its impact on DSGH recovery were analyzed. A new formula for calculating the yield of DSGH was proposed. Utilization status and development trend of DSGH were introduced in detail. A scheme of fully resourceful utilization of DSGH was proposed.